Youth Participation and Challenges in Rural Agribusiness: A Study of Agripreneurs in Haryana, India - Jyoti, Seema Rani; Khushbu (Archives of Current Research International, 2024)
This study explores the participation of rural youth in agribusiness enterprises, focusing on their involvement, motivations, experience, and the challenges they encounter. However, despite its significance, rural youth often face obstacles such as limited access to resources, market linkages, and relevant skills. To address these issues, this research was conducted across four districts of Haryana—Bhiwani, Jind, Hisar, and Kurukshetra—where Agri Business Centers are located. A total of 60 agripreneurs formed the study sample and data were gathered through structured interviews based on a well-validated questionnaire. Results revealed that over half of the participants had 3 to 5 years of experience in farming and agribusiness. Key motivational factors for engaging in agribusiness included well-developed entrepreneurial skills and easy access to raw materials. Most respondents were involved in livestock management and food processing activities. However, they faced significant challenges, such as difficulties in obtaining certification, lack of access to loans, limited awareness of modern agricultural technologies, and low confidence levels. The study highlights the need for targeted interventions to overcome financial, infrastructural, and skill-related barriers faced by rural youth in agribusiness, recommending enhanced access to credit, certification support, entrepreneurial training, and public-private partnerships to foster sustainable rural development.